An Infectious Disease and Mortality Survey in a Population of Free-Ranging African Wild Dogs and Sympatric Domestic Dogs. (31st March 2013) - Flacke, G.; Becker, P.; Cooper, D.; Szykman Gunther, M.; Robertson, I.; Holyoake, C.; Donaldson, R.; Warren, K.
Abstract : Disease can cause declines in wildlife populations and significantly threaten their survival. Recent expansion of human and domestic animal populations has made wildlife more susceptible to transmission of pathogens from domestic animal hosts. We conducted a pathogen surveillance and mortality survey for the population of African wild dogs ( Lycaon pictus ) in KwaZulu-Natal (KZN), South Africa, from January 2006–February 2007. Samples were obtained from 24 wild dogs for canine distemper virus (CDV) and canine parvovirus (CPV) serological testing. Data were collected on the presence of CDV, CPV, and rabies virus in the KZN domestic dog ( Canis familiaris ) population from 2004–06. The presence of these pathogens was confirmed in domestic dogs throughout KZN. Wild dogs exhibited 0% and 4.2% prevalence for CDV and CPV antibodies, respectively. In 2006 the largest wild dog pack in KZN was reduced from 26 individuals to a single animal; disease due to rabies virus was considered the most probable cause. This study provides evidence that CDV, CPV and rabies are potential threats to African wild dog conservation in KZN. The most economical and practical way to protect wild dogs from canine pathogens may be via vaccination of sympatric domestic dogs; however, such programmes are currently limited.